Top ten myths in concrete construction [videorecording] - Thunder Bay Productions; Portland Cement Association (Skokie, Ill. : Portland Cement Association, 2005)
Takes a candid look at ten popular, but mistaken ideas that exist in concrete construction. Using examples, interviews, and demonstrations, this video program exposes and explains the most common misconceptions in the industry
Title from title screen
Associate producer, videographer, writer, Gary Mitchell
DVD format
Keywords: Concrete construction; Concrete